Knowledge-based economics can[1] be achieved by using the role of knowledge to commercialize university research result in the agroindustry activities. Collaboration as a model to realize transfer of technology between university and agroindustry is institutional proven model. The use of science and technology in the new era of knowledge-based economy is expected to contribute in improvement of nation competitiveness. Decision making in the complex, dynamic and probabilistic problem as founde - Widadi W. Widayat; Irawadi Jamaran; Bunasor Sanim; Marimin .; Amril Aman; Djati Kerami (Forum Pasca Sarjana, 2011)
Knowledge-based economics can[1] be achieved by using the role of knowledge to commercialize university research result in the agroindustry activities.  Collaboration as a model to realize transfer of technology between university and agroindustry is institutional proven model.  The use of science and technology in the new era of knowledge-based economy is expected to contribute in improvement of nation competitiveness.  Decision making in the complex, dynamic and probabilistic problem as founded in the collaboration model needs analytical tools such as analytical hierarchy process (AHP), fuzzy inference system (FIS) and artificial neural network (ANN) as well as the combination of both techniques which is one of the best method for designing Model of University and Small, Medium Agroindustry collaboration in transferring technology as a reliable model in the future.  Takagi-Sugeno-Kang Inference System is used to have input-output mapping using fuzzy logic, and artificial neural network with back propagation mechanism is used to get optimal membership parameters.  Knowledge acquisition of the experts are needed together with ANFIS (adaptive network fuzzy inference system).  After having simulation using Matlab program by combining ANFIS for Fuzzy membership function and certainty factor for non fuzzy membership function, recommendation is made on networking as collaboration pattern on transferring of innovation technology is the best choice, and fishery agroindustry using incubator technology as institution model is the best evidence of certainty factor achieved.   Key words: collaboration model, technology transfer, AHP, neuro-fuzzy and takagi sugeno inference 6) Fakultas Matematika dan IPA, Universitas Indonesia